Impact of AI on Sustainable Development - Nadia Mahmood Hussien; Yasmin Makki Mohialden; Nada Thanoon Ahmed (Journal of Public Representative and Society Provision, 2026)
Automation has changed industrial production; artificial intelligence (AI) is next. AI allows machines and systems to work with people and other living things, and this research examines how AI may establish sustainable economic models. This research examines how computer science, through AI, quick machine learning, and sustainable development (SD), can modify consumer and production habits to accomplish the UN 2030 Agenda's Sustainable Development Goals. The study shows that AI might transform SBMs. AI can optimize resource allocation, boost efficiency, and eliminate waste. AI can create new sustainable products and services. AI sustainability faces certain obstacles, according to the research. AI implementation may be costly, and safely using AI systems can be difficult. The study concludes that AI might boost sustainability. Before using AI in SBMs, examine the pros and cons.